2016
DOI: 10.1371/journal.pone.0163917
|View full text |Cite
|
Sign up to set email alerts
|

Strong or Weak Handgrip? Normative Reference Values for the German Population across the Life Course Stratified by Sex, Age, and Body Height

Abstract: Handgrip strength is an important biomarker of healthy ageing and a powerful predictor of future morbidity and mortality both in younger and older populations. Therefore, the measurement of handgrip strength is increasingly used as a simple but efficient screening tool for health vulnerability. This study presents normative reference values for handgrip strength in Germany for use in research and clinical practice. It is the first study to provide normative data across the life course that is stratified by sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
143
8
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(186 citation statements)
references
References 41 publications
21
143
8
14
Order By: Relevance
“…The present analyses used maximum value of the dominant hand as the exposure variable. 26 Combined grip strength (the sum of the largest reading from each hand) or average values were further included in sensitivity analyses.…”
Section: Handgrip Strength (Exposure Variable)mentioning
confidence: 99%
“…The present analyses used maximum value of the dominant hand as the exposure variable. 26 Combined grip strength (the sum of the largest reading from each hand) or average values were further included in sensitivity analyses.…”
Section: Handgrip Strength (Exposure Variable)mentioning
confidence: 99%
“…; Mitchell et al. ; Steiber ). At its extreme, sarcopenia is seen in 5–13% of people between 60 and 70 years of age, which increased to 50% of those >80 years of age (Metter et al.…”
Section: Introductionmentioning
confidence: 99%
“…The aging process is inherent to the human condition, and involves a loss of muscle mass, muscle function, and a generalized increase in frailty. Loss of muscle mass and function occurs at a predictable rate throughout adulthood, with evidence of muscle mass loss from 30 years of age (Kallman et al 1990;Mitchell et al 2012;Steiber 2016). At its extreme, sarcopenia is seen in 5-13% of people between 60 and 70 years of age, which increased to 50% of those >80 years of age (Metter et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…With the same goal, Araujo et al 15 conducted a populational study of pinch strength with pinch gauge™ dynamometer and concluded that the strength of lateral pinch in the male gender presents an average of 9.9±1.9 kgf and 6.7±1.4 kgf in the female gender. Studies related to normative data for grip and pinch are presented in different countries and serve as a reference in clinical practice in order to compare possible changes of grip strength and pinch, arising from different lesions of the upper limb 6,16 . Tang et al 17 describe that changes in biomechanical parameters of the wrist can be an important cause of diseases and dysfunctions.…”
Section: Introductionmentioning
confidence: 99%